"Cheese coffee" / Evan Gale David Francis Motijal, Farah Diyanah Hairi and Nurul Shafiqah Izzatie Mohd Fazli - David Francis Motijal, Evan Gale; Hairi, Farah Diyanah; Mohd Fazli, Nurul Shafiqah Izzatie (2017)
Our business name is Cheese Coffee. Our business produces a beverage in term of different flavours of coffee with the uniqueness of cream cheese as the topping. We are more focus to marketing and selling our product since we are a new comer in food industry. The location, where our product will be selling which is the place that famous and have many people and foods as well as tourist, especially who are from Singapore and also the local residents. Our target market is mostly on average at 13 to 28 years old. This is because at this average ages are more attractive to buy our drinks. Other than that, the price, that we are offered are very affordable for those people is according to data collection on the population that we have made.